Wise drives [hard disk drive]. - Hughes, G.F.
Considers how smarter disk drives could herald speedier data mining, tighten computer security, and improve data storage reliability, but only if drive and computer makers and software designers can agree on new interface standards.
Keywords: Computer security; Data mining; Data storage reliability; Hard disk drive; Intelligent disk drives; Interface standards; Software design